«Green» Vallejo in The Black Heralds - Hart, Stephen M. (2019)
Running counter to the focus on «blackness» and «pessimism» that some critics emphasise in their assessment of César Vallejo’s first published collection of poems, in this essay I use an eco-critical approach in order to focus on the role played by greenness in Vallejo’s 1919 collection, The Black Heralds. I start with the early poems such as «Phosphorence» and «Vegetal Transpiration» and argue that they are important for an understanding of Vallejo’s primordial reliance on nature, as are those poems in The Black Heralds that focus on greenness. I then pass to an analysis of the ways in which Vallejo portrays his incestuous relationship with his niece via the heretical account of Christ’s sexual relationship with Mary Magdalene in poems such as «Nervy Frenzy of Anguish», «Comunion» and «September», and suggest that these reveal a «green» side to Vallejo’s poetic persona. Finally I draw on Claude Lévi-Strauss’s theory of the «cooked» and the «uncooked» and his related theory of the prohibition of incest as underpinning human culture in order to suggest that Vallejo’s poetic persona sought the sweetness of a world in which he could escape the need to communicate through the exchange of words in the same way that he refused to exchange women, and thereby, in Lévi-Strauss’s words, «vivre entre soi».